2020
DOI: 10.1109/tai.2021.3055167
|View full text |Cite
|
Sign up to set email alerts
|

A Neural State Pushdown Automata

Abstract: In order to learn complex grammars, recurrent neural networks (RNNs) require sufficient computational resources to ensure correct grammar recognition. A widely-used approach to expand model capacity would be to couple an RNN to an external memory stack. Here, we introduce a "neural state" pushdown automaton (NSPDA), which consists of a digital stack, instead of an analog one, that is coupled to a neural network state machine. We empirically show its effectiveness in recognizing various context-free grammars (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We implemented several variations of the recurrent state-function s k for the estimator described above. In preliminary experiments, we found that the LSTM state function and the RNN-SNE (a more expensive, but expensive extension of our estimator [27]) yielded the most consistent performance. Therefore, we report the performance using an LSTM as a state cell for all algorithms and RNN-SNE using BPTT and SAB (since we found that SAB worked best when using LSTM state functions) 1 .…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…We implemented several variations of the recurrent state-function s k for the estimator described above. In preliminary experiments, we found that the LSTM state function and the RNN-SNE (a more expensive, but expensive extension of our estimator [27]) yielded the most consistent performance. Therefore, we report the performance using an LSTM as a state cell for all algorithms and RNN-SNE using BPTT and SAB (since we found that SAB worked best when using LSTM state functions) 1 .…”
Section: Methodsmentioning
confidence: 88%
“…Iterative Refinement: This procedure can be seen as locally decoding data process aimed at improving the memory retention ability of recurrent neural networks (RNNs) [1,27,2]. The neural decoder used with this process essentially reconstructs images from a compressed representation and iterative refinement formulates compression as a multi-step reconstruction problem over a finite number of passes, K. Consider a 2D image I and decompose it into a set of P image patches, or I = {p 1 , • • • , p j , • • • , p P } (i.e non-overlapping for JPEG, overlapping for JP2).…”
Section: Hybrid Nonlinear Estimator For Iterative Decodingmentioning
confidence: 99%
“…Prior work [10,52,41] has shown that initializing a network with prior knowledge can yield improved generalization while training. In such cases, the weights of the network which are not programmed (ie.…”
Section: Discussionmentioning
confidence: 99%
“…Many neural network models take the form of a first order (in weights) recurrent neural network (RNN) and have been taught to learn context free and context-sensitive counter languages [17,9,5,64,70,56,48,66,8,36,8,67]. However, from a theoretical perspective, RNNs augmented with an external memory have historically been shown to be more capable of recognizing context free languages (CFLs), such as with a discrete stack [10,55,61], or, more recently, with various differentiable memory structures [33,26,24,39,73,28,72,25,40,41,3,42]. Despite positive results, prior work on CFLs was unable to achieve perfect generalization on data beyond the training dataset, highlighting a troubling difficulty in preserving long term memory.…”
Section: Related Workmentioning
confidence: 99%
“…Hierarchical RNNs, such as the Clockwork RNN [14], Phased LSTM [16], and Hierarchical Multiscale RNN [3], solve this limitation by modifying the architecture to easily encode long-term dependencies in the hidden state. Most of the effort of the literature focus on architectural modifications [3,15,16]. Another line of research explores the use of online algorithms to train RNNs [18,?,23].…”
Section: Related Workmentioning
confidence: 99%